Selective pressure of biphenyl/polychlorinated biphenyls on the formation of aerobic bacterial associations and their biodegradative potential - Egorova, Darya; Kir'yanova, Tatyana; Pyankova, Anna; Anan'ina, Ludmila; Plotnikova, Elena (Folia microbiologica, 2021)
Unique bacterial associations were formed in the polluted soils from territory of the industrial factories Open Joint Stock Company "The Middle Volga Chemical Plant," Chapaevsk, Russia and Open Joint Stock Company "Lubricant Producing Plant," Perm, Russia. This study evaluates the influence of the biphenyl/polychlorinated biphenyls (PCB) on the formation of aerobic bacterial associations and their biodegradative potential. Enrichment cultivation of the soil samples from the territories of these industrial factories with PCB (commercial mixture Sovol) was lead for forming aerobic bacterial enrichment cultures showing a unique composition. The dominating in these bacterial cultures was the phylum Proteobacteria (Beta- and Gammaproteobacteria). Using biphenyl as a carbon source led to decrease of biodiversity in the final stable bacterial associations. Periodic cultivation experiments demonstrated that the association PN2-B has a high degradative potential among the six studied bacterial associations. PN2-B degraded 100% mono-chlorobiphenyls (94.5 mg/L), 86.2% di-chlorobiphenyls (22.3 mg/L), 50.9% Sovol, and 38.4% Delor 103 (13.8 mg/L). Qualitative analysis of metabolites showed that association performed transformation of chlorobenzoic acids (PCB degradation intermediates) into metabolites of citrate cycle. Twelve individual strain-destructors were isolated. The strains were found to degrade 17.7-100% PCB1, 36.2-100% PCB2, 18.8-100% PCB3 (94.5 mg/L), and 15.7-78.2% PCB8 (22.3 mg/L). The strains were shown to metabolize chlorobenzoic acids formed during degradation of chlorobiphenyls. A unique ability of strains Micrococcus sp. PNS1 and Stenotrophomonas sp. PNS6 to degrade ortho-, meta-, and para-monosubstituted chlorobenzoic acids was revealed. Our results suggest that PN2-B and individual bacterial strains will be perspective for cleaning of the environment from polychlorinated biphenyls.
Keywords: Soil Pollutants; aerobní bakterie; půdní mikrobiologie; Polychlorinated Biphenyls; Biodegradation, Environmental; látky znečišťující půdu; polychlorované bifenyly; Bacteria, Aerobic; Soil Microbiology; Microbial Interactions; biodegradace; mikrobiální interakce